AI-powered Solutions for Casualty Assessment in Drug Safety and Patient Care - Sharma, Himanshu; Mahajan, Shushank; Garg, Nitika; Chauhan, Samrat; Saini, Monika; Singh, Thakur Gurjeet; Dhankhar, Sanchit; Mittal, Pooja (New Emirates Medical Journal, 2024)
ObjectiveAn adverse drug reaction is defined as “an appreciably harmful or unpleasant reaction, resulting from an intervention related to the use of a medicinal product, which warrants prevention or specific treatment, alteration of the dosage regimen, or withdrawal of the product, as it predicts hazard from future administration.”MethodologyCurrently used to report such responses, the International Classification of Diseases will soon incorporate WHO's Adverse Reaction Terminology. A medication's bad effects can fall into one of six types, each having its own mnemonic: withdrawal, therapeutic failure, dose-and time-related, non-dose-related, weird, increased withdrawal, and withdrawal overall (time-related). Factors such as timing, illness pattern, investigation findings, and retesting the medicine could be useful in pinpointing the reason for a suspected adverse drug reaction. Management includes treating the effects of the medication specifically as well as, if feasible, stopping it altogether.ResultsReporting suspected adverse medication reactions is important. Monitoring techniques are able to identify responses and establish connections. There is many software that is used to report and monitor adverse drug reaction responses. Various Pharmacovigilance companies use AI technology to utilize this method to record signals, communicate, and solve new issues in order to limit or avoid harm because of large data size.
Keywords: Adverse drug reaction